Analysis for inter turn stator fault with load variation in Induction Motor - Cherif, Hakima; Maamir, Madiha; Chehaidia, Seif Eddine (جامعة الوادي Université ofEl-Oued, 2023)
This paper investigates the impact of load variation on the diagnosis of inter-turn stator faults in induction machines. The proposed detection technique relies on the analysis of stator current using the discrete wavelet transform (DWT) in both normal and faulty states of the machine. The energy of the approximation and detail signals obtained from DWT provides valuable information about the machine's health and the severity of the inter-turn stator faults. Experimental tests were conducted using a dSpace 1104 signal card-based interface to study the load effects in detecting and diagnosing stator inter-turn short circuit faults in induction motor
Article
Keywords: Induction Motor, fault detection, diagnosis, Inter Turns Short Circuit Fault (ITSC), Discrete Wavelet Energy (DWE).